POTENSI TUMBUHAN BANGKAL (Nauclea Orientalis) UNTUK PENGENDALIAN BAKTERI Aeromonas Hydrophila - Siti Aisiah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
The purpose of this study was obtained method of controlling diseases caused by Aeromonas hydrophila in fish farming is environmentally friendly. In this study the sensitivity of the test A. hydrophila, a minimum test konsentari inhibiting A.hydrophila (MIC test) and toxicity test on tilapia. The design used for toxicity tests iscompletely randomized design with 4 treatments it A = Fish injected with extracts bangkal concentration of 20 %, B = Fish injected with extracts bangkal concentration of 40 %, C = Fish injected with extracts of 80 % concentration bangkal, and D =Control ( fish not injected ), repeated 3 times. This treatment was obtained from theresults of the sensitivity test antibacterial bangkal inhibition and has the power to killmost of the bacteria against A. hydrophila is bangkal leaf extract with distilled watersolvent. MIC testing showed that the extract bangkal - distilled water has a minimum of 20 % inhibition of the bacterial activity A. hydrophila. Results of toxicity tests conducted on tilapia with a concentration of 20 %, 40 % and 80 % mortality of tilapia under 50 %. Haematological observation that eretrosit, leokosit, blood plasm, hematocrit and leokokrit in each treatment is still in the normal range. The water quality parameters, dissolved oxygen, pH, ammonia, CO2 and temperature can still support the normal life of tilapia.